Team Boundary Activity: Its Mediating Role in the Relationship Between Structural Conditions and Team Innovation. (June 2014) - Somech, Anit; Khalaili, Amira
The purpose of this study is to broaden our understanding of team boundary activities in promoting team innovation. The model examines the mediating role of boundary activities in the relationship between the structural variables of inter-team goal interdependence and team functional heterogeneity and team innovation. Sixty teams from high-technology companies were studied involving 196 team members and their 60 corresponding team leaders and unit managers to whom the leaders report. Results identified two dimensions of boundary activities: boundary-loosening activities and boundary-tightening activities. Overall, the results of the structural equation model confirmed the mediating role of team boundary activity. The results indicated a positive relationship between the two structural variables and boundary-loosening activities, a negative relationship between functional heterogeneity and boundary-tightening activities, and a positive relationship between the two dimensions of boundary activities and team innovation. Implications, limitations, and directions for further research on team boundary activities are discussed.